Ways to Improve Hospital Quality - A Health System Perspective; Comment on "Hospitals Bending the Cost Curve With Increased Quality: A Scoping Review Into Integrated Hospital Strategies" - Ansgar Wuebker (Kerman University of Medical Sciences, 2023)
Wackers and colleagues' scoping review provides an informative and well-structured overview of hospital-based case studies focusing on integrated hospital strategies that seek to improve quality, while reducing or containing costs. Wackers et al take a hospital level perspective and evaluate facilitators and barriers to the successful implementation of those hospital strategies. I complement the hospital level perspective of Wackers et al with an analysis from a health system perspective. Regulations at the superordinate system level might influence decisions at the hospital level that are relevant for costs and quality of care. In this commentary, I discuss how interventions at the system level might affect hospital quality. The results suggest that especially competition between hospitals, pay for performance (PfP) initiatives in combination with publication of quality information, but also greater experience of hospital staff (as proxied by the volume outcome relationship) may provide impulses for improving quality of care.